2017
DOI: 10.1016/j.foodchem.2016.11.153
|View full text |Cite
|
Sign up to set email alerts
|

The influence of phytochemical composition and resulting sensory attributes on preference for salad rocket (Eruca sativa) accessions by consumers of varying TAS2R38 diplotype

Abstract: HighlightsTAS2R38 bitterness perception does not wholly determine liking of rocket.Hotness is the main attribute on which consumers base their liking not bitterness.Some consumers prefer mild sweet accessions low in glucosinolates and pungent VOCs.Glucoraphanin imparts no significant influence on liking or sensory perceptions.Sugar-glucosinolate/isothiocyanate ratios are important for hotness perceptions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
31
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 32 publications
4
31
0
Order By: Relevance
“…However, some research has shown that this does not necessarily translate into whether an individual will base their liking upon this sensitivity . A study by Bell et al . which determined TAS2R38 diplotypes of 69 individuals reported that “supertaster” status did not have a significant impact upon liking of different rocket salad accessions.…”
Section: Bitter Taste Of Glucosinolates and Isothiocyanatesmentioning
confidence: 99%
See 4 more Smart Citations
“…However, some research has shown that this does not necessarily translate into whether an individual will base their liking upon this sensitivity . A study by Bell et al . which determined TAS2R38 diplotypes of 69 individuals reported that “supertaster” status did not have a significant impact upon liking of different rocket salad accessions.…”
Section: Bitter Taste Of Glucosinolates and Isothiocyanatesmentioning
confidence: 99%
“…and D'Antuono et al . reported that the presence of 4‐hydroxyglucobrassicin (an indolic GSL) within rocket leaf tissues was associated with such pleasant traits, and Bell et al . also reported that relatively “minor” GSLs contributed toward increased liking for a subset of consumers.…”
Section: Bitter Taste Of Glucosinolates and Isothiocyanatesmentioning
confidence: 99%
See 3 more Smart Citations